Analisis Kinerja Pegawai Kantor Desa Dalam Memberikan Pelayanan Administrasi kepada Masyarakat: - Andri Yusuf Siregar; Sri Sudiartri (VISA: Journal of Vision and Ideas, 2022)
Several elements influence the quality of public or public services, one of which is the employee's performance in carrying out public services. The ability of employees has a significant impact on the quality of government services. Village apparatus are public service officials who have the authority and responsibility for providing services to the community or the general public, and who assist the village head in carrying out his duties in order to be able to provide services in accordance with the community's wishes and needs. As a result, village officials are required and mandated to have commitment, as well as abilities and skills, feelings of sincere concern, and a high sense of empathy in carrying out their duties. The goal of this research is to examine village office personnel' performance in providing administrative services to the community in Laut Dendang Village, as well as to determine what variables impede and support their success. Survey research with qualitative descriptive methodologies is the research method. Purposive sampling yielded 5 informants. Interview guidelines, literature review, and documentation were used as data collection strategies. Data reduction, data display, and data verification procedures are all used in data analysis. According to the findings of the interviews, all of the informants provided information or comments indicating that the village office employees' performance met the standardization and was appropriate in providing public services based on the areas of the research emphasis, namely 1) Achievement. 2) Abilities 3) The ability to lead. The behavior (attitude) does not fulfill the public service criteria. This study demonstrates that enhancing employee performance yields positive results in terms of community service. Keywords: Performance, Village Office Employees, Administrative Services, Community